Asuhan Keperawatan pada Tn. M dengan Post Operasi Craniotomy : Cedera Kepala Sedang di Ruang Mawar 2 RSUD Dr. Soeselo Kabupaten Tegal - Isnaeni Rahmawati; Ahmad Zakiudin; Tati Karyawati; Nur Umi Aminatussholihah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Head injury is a health problem, one of the main factors of which is traffic accidents. Head injuries occur when the head structure experiences an external impact that has the potential to disrupt brain function. The severity varies, from minor injuries, bruising, swelling, bleeding, dislocation, skull fractures, to concussions. The mechanism of impact and the severity of the injury are determining factors in the type of injury experienced (Poniati & Dani Saputro, 2023). Head injuries can range from minor injuries to the scalp to serious damage to the brain. This injury is usually caused by impact, such as falling, accidents, being hit by sharp objects, being hit or the head hitting something (Rahmawan, 2023).